Apolipoprotein A5 and triglyceridemia. Focus on the effects of the common variants - Hubacek, Jaroslav A (Clinical chemistry and laboratory medicine, 2005)
High plasma levels of triglycerides are an independent risk factor for the development of cardiovascular disease. Apolipoprotein A5 (APOA5) is a new member of the apolipoprotein APOA1/C3/A4 gene cluster, found by comparative sequencing analysis. The importance of the APOA5 gene for determination of plasma triglyceride levels has been suggested by the creation of transgenic and knock-out mice (transgenic mice displayed significantly reduced triglycerides, whereas knock-out mice had a high level of triglycerides). It has now been clearly established that distinct polymorphisms in the APOA5 gene consistently influence plasma triglycerides in a wide range of human populations, although some differences between ethnic groups and males and females were described. The possible roles of APOA5 variants in determining the risk of myocardial infarction and coronary artery disease development, as well as in the determination of low-density lipoprotein-particle size or plasma concentrations of C-reactive protein and high-density lipoprotein-cholesterol, are also summarized.
Keywords: Hypertriglyceridemia; Apolipoprotein A-V; Triglycerides; Apolipoproteins; hypertriglyceridemie; Animals; triglyceridy; apolipoproteiny A; apolipoproteiny; Coronary Disease; Humans; lidé; apolipoprotein A-V; koronární nemoc; zvířata; Apolipoproteins A